(untitled) (Window of Public Health Journal, 2025)
Work productivity comes from the word productive, which refers to all activities that cause use. Based on data from the International Labor Organization (ILO) states that every year, as many as two workers die due to work accidents caused by fatigue factors. The study aimed to determine the factors related to work productivity in employees at the Menara Universitas Muslim Indonesia. The type of research used was a sectional study. The population in this study was 156 employees. The sample in this study was 106 employees using cluster techniques divided by division. Data analysis was carried out univariately and bivariate using chi-square. The study showed a relationship between eye fatigue and work productivity, which obtained a value (p = 0.000 <0.05). There was a relationship between lighting and work productivity, which obtained a value (p = 0.007 <0.05). There was no relationship between length of work and work productivity, which obtained a value (p = 0.161> 0.05). There is no relationship between Length of Service and Work Productivity, which obtained a value (p = 0.441 > 0.05). This study concludes that there is a relationship between eye fatigue, lighting, and Work Productivity at the Muslim University of Indonesia Tower in 2023, while there is no relationship between length of service, length of service, and Work Productivity at the Muslim University of Indonesia Tower in 2023. As for suggestions to reduce eye fatigue at the UMI tower, the lighting should be improved because eye fatigue can also be caused by poor lighting.